Regulation of innate immune responses by rabies virus. Issue 5 (22nd September 2022) - Zhang, Haili; Huang, Jingbo; Song, Yumeng; Liu, Xingqi; Qian, Meichen; Huang, Pei; Li, Yuanyuan; Zhao, Ling; Wang, Hualei
Abstract: Rabies virus (RABV) is an infectious and neurotropic pathogen that causes rabies and infects humans and almost all warm‐blooded animals, posing a great threat to people and public safety. It is well known that innate immunity is the critical first line of host defense against viral infection. It monitors the invading pathogens by recognizing the pathogen‐associated molecular patterns and danger‐associated molecular patterns through pattern‐recognition receptors, leading to the production of type I interferons (IFNα/β), inflammatory cytokines, and chemokines, or the activation of autophagy or apoptosis to inhibit virus replication. In the case of RABV, the innate immune response is usually triggered when the skin or muscle is bitten or scratched. However, RABV has evolved many ways to escape or even hijack innate immune response to complete its own replication and eventually invades the central nervous system (CNS). Once RABV reaches the CNS, it cannot be wiped out by the immune system or any drugs. Therefore, a better understanding of the interplay between RABV and innate immunity is necessary to develop effective strategies to combat its infection. Here, we review the innate immune responses induced by RABV and illustrate the antagonism mechanisms of RABV to provide new insights for the control of rabies. Abstract : Host innate immune response will be activated upon RABV infection to regulate the replication of RABV, including interferon response, autophagy, apoptosis, inflammatory response, and mitochondrial dysfunction. Meanwhile, RABV has formed a variety of escape strategies in the process of co‐evolution with hosts, mainly through regulating host innate immune pathways by viral proteins P, M, and N to promote self‐replication.